The Theory of Groups - Macdonald, Ian D. (Glasgow Oxford University Press, 1968)
The Theory of Groups. This book provides a sustantial first course in the theory of groups that is suitable for undergraduate courses in universities and will be of interest to those teaching modern mathematics in school.
Keywords: Social Studies